Antihypertensive effect of surimi prepared from olive flounder (Paralichthys olivaceus) by angiotensin-I converting enzyme (ACE) inhibitory activity and characterization of ACE inhibitory peptides. (May 2019) - Oh, Jae-Young; Kim, Eun-A; Lee, Hyogeun; Kim, Hyun-Soo; Lee, Jung-Suck; Jeon, You-Jin
Graphical abstract: Highlights: Flounder is a potential source of surimi with antihypertensive effects. Flounder surimi digest had ACE inhibitory activity and increased NO production. Flounder surimi decreased systolic blood pressure in spontaneously hypertensive rats. Bioactive FS peptides bind to ACE in silico, supporting the antihypertensive effects. Abstract: In this study, we investigated the physicochemical characteristics of flounder surimi (FS) and surimi gel (FSG). We analyzed the proximate composition, heavy metal content, and amino acid composition of FS and the gel strength and whiteness of FSG. In spontaneously hypertensive rats, the oral administration of FS significantly decreased systolic blood pressure. We further evaluated the antihypertensive activity of an FS digest (FSD) using an in vitro gastric model. FSD had significant ACE inhibitory activity and increased nitric oxide (NO) levels in human umbilical vein endothelial cells. We purified and identified three peptides from FSD by gel filtration chromatography and quadrupole time of flight electrospray ionization mass spectrometry. We predicted the tertiary structure of ACE for docking simulation. The bioactive peptides from FS showed successful binding to ACE (PDB ID: 1O86) with negative binding energy and negative CDOCKER interaction energy in an in silico docking analysis. These results showed that FSD functions as an antihypertensive agent and FS could be a beneficial ingredient in the nutraceutical, pharmaceutical, and functional food industries.